ANALISIS KINERJA KOMPREHENSIF DENGAN BALANCED SCORECARD PADA PT. KERETA API INDONESIA (Studi Kasus Pada PT. KAI DAOP IV Semarang) - Aloysius Christian Rico Aditama; Endang Kiswara (Diponegoro Journal of Accounting, 2013)
This study aims to measure the performance of PT. Kereta Api Indonesia uses comprehensive performance measurement. This study uses the Balanced Scorecard, which is used to measure the performance of the financial perspective, customer perspective, internal business perspective, and learning and growth perspectives. Data for this study were 32 employee questionnaires, 305 questionnaires customer, and the annual report of PT Kereta Api Indonesia in 2011.Results indicate that the performance of PT. Kereta Api Indonesia as a whole is good. In the financial perspective with the indicators of liquidity ratios, solvency ratios, and profitability ratios showed a good performance. For the customer perspective shows good performance with a value of 3,408. At the company's internal business perspective  can already do a good innovation. And for growth and learning perspective suggests that the level of employee satisfaction was satisfactory with a value of 3.268. From the research data, it can be concluded that by using the Balanced Scorecard can provide performance evaluation PT Kereta Api Indonesia to be more performance in the next period.